2013
DOI: 10.1038/nmeth.2557
|View full text |Cite
|
Sign up to set email alerts
|

The CRAPome: a contaminant repository for affinity purification–mass spectrometry data

Abstract: Affinity purification coupled with mass spectrometry (AP-MS) is now a widely used approach for the identification of protein-protein interactions. However, for any given protein of interest, determining which of the identified polypeptides represent bona fide interactors versus those that are background contaminants (e.g. proteins that interact with the solid-phase support, affinity reagent or epitope tag) is a challenging task. While the standard approach is to identify nonspecific interactions using one or m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
1,417
2
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,503 publications
(1,491 citation statements)
references
References 51 publications
12
1,417
2
4
Order By: Relevance
“…PICh nominated ∼80 proteins that were enriched more than twofold at deprotected mouse telomeres (Supplemental Table S1). Comparison with the CRAPome (Mellacheruvu et al 2013) showed that a large fraction of the candidates is likely contaminants (Supplemental Table S1), as had been noted previously (Bartocci et al 2014). One protein, PHF11, was not an obvious contaminant.…”
Section: Identification Of Phf11 As a Ddr Factorsupporting
confidence: 59%
“…PICh nominated ∼80 proteins that were enriched more than twofold at deprotected mouse telomeres (Supplemental Table S1). Comparison with the CRAPome (Mellacheruvu et al 2013) showed that a large fraction of the candidates is likely contaminants (Supplemental Table S1), as had been noted previously (Bartocci et al 2014). One protein, PHF11, was not an obvious contaminant.…”
Section: Identification Of Phf11 As a Ddr Factorsupporting
confidence: 59%
“…Following concentration, the complexes were subjected to SDS–PAGE, excised and further processed by trypsin digestion for LC‐MS/MS analysis (Fig EV1B). Amongst the strongest LGP2 interactors in both the type I IFN and poly(I:C)‐treated samples, we identified the endoribonuclease Dicer, as well as several known co‐factors of Dicer, including TRBP (HIV TAR RNA‐binding protein), PACT (protein activator of PKR) and PKR (protein kinase R; Fig 1B), all of which appear at negligible frequency in the “Contaminant Repository for Affinity Purification” databases for FLAG IPs (Mellacheruvu et al , 2013). …”
Section: Resultsmentioning
confidence: 99%
“…To eliminate background contaminants the CRAPome database was used (30). CRAPome is a repository of negative controls generated by previous proteomics experiments and calculates a score for the interaction data as 1-number of experiments the protein is found in the database/total number of experiments in the database.…”
Section: Bioinformatic Analysis Of Drug Pulldown Datamentioning
confidence: 99%
“…We computed the probability of true interaction using the SAINT algorithm (29) and opposed it to the magnitude of spectral count reduction upon competition with the free compound and we also considered the frequency of appearance in negative control experiments found in the CRAPome database (30). Altogether, this allowed us to capture the core target spectrum of PKC412 in Ewing sarcoma cell line (Fig.…”
Section: Identification Of a Ewing Sarcoma Specific Synergy Between Pmentioning
confidence: 99%